The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/cncr.32603
|View full text |Cite
|
Sign up to set email alerts
|

Is surveillance imaging in pediatric patients treated for localized rhabdomyosarcoma useful? The European experience

Abstract: BACKGROUND: After the completion of therapy, patients with localized rhabdomyosarcoma (RMS) are subjected to intensive radiological tumor surveillance. However, the clinical benefit of this surveillance is unclear. This study retrospectively analyzed the value of off-therapy surveillance by comparing the survival of patients in whom relapse was detected by routine imaging (the imaging group) and patients in whom relapse was first suspected by symptoms (the symptom group). METHODS: This study included patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 31 publications
3
34
0
Order By: Relevance
“…In our cohort during the follow up there were 26 events, of which 24 were local events. This result was consisted with other reports, that the most common treatment failure (including disease progression and relapse) was local failure, and maintaining local control would benefit prognosis substantially [7,8,22].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In our cohort during the follow up there were 26 events, of which 24 were local events. This result was consisted with other reports, that the most common treatment failure (including disease progression and relapse) was local failure, and maintaining local control would benefit prognosis substantially [7,8,22].…”
Section: Discussionsupporting
confidence: 86%
“…Clinical data during and after treatment were recorded. Frequency of off-therapy surveillance was every 3 months for the first year, every 4 months for the second and third year, and once a year for the fourth and fifth year [8]. Clinical physical examination, blood routine and biochemical tests, head and neck CT or MRI with or without contrast, and chest CT or chest X-ray were required for surveillance, and PET-CT was optional to replace all imaging examinations.…”
Section: Follow Upmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that the patterns of disease progression and relapse of this cohort were mainly local, which was consistent with other published reports [9,21]. A cure for RMS depends rstly on local control (eradication of the primary tumor by surgery and/or RT), then on systemic control (eradication of the micro and metastatic residual) [5].…”
Section: Discussionsupporting
confidence: 91%
“…To determine whether delayed diagnosis contributes to such poor outcomes in some patients, the EpSSG conducted a retrospective study comparing 78 patients who had imaging performed routinely to 121 patients who had imaging performed on the basis of symptoms alone. The patients who received routine imaging had their disease detected earlier than those who did not (8 versus 12 months); however, this did not improve survival, suggesting that the poor outcomes cannot be explained solely by delayed diagnosis 38 .…”
Section: Advances In the Treatment Of Rmsmentioning
confidence: 94%